2003
DOI: 10.3354/meps246105
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pfiesteria piscicida growth and encystment parameters using a numerical model

Abstract: In the past decade, there has been growing interest in understanding the physiological ecology and life cycle of toxic forms of Pfiesteria piscicida. However, transformations among noninducible (NON-IND; formerly described as nontoxic) stages have received less attention despite the fact that NON-IND stages are found in nature and may be ecologically important as prey and predators. NON-IND stages are also mixotrophic and have the ability to retain and utilize prey chloroplasts in a process termed 'kleptoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…3A). Laboratory observations have confirmed that the light does, indeed, enhance the growth of zoospores (Anderson et al 2003b). In the model, this effect is due to the photosynthetic activity of kleptochloroplasts of zoospores, which is consistent with experimental studies on Pfiesteria nutrient uptake 39 (C) Sensitivity of the model-estimated time period of the plateau phase of change in zoospore abundance, the maximal abundance at the plateau phase and the abundance at the end of the 14 d experiment to additional model parameters used in the third modeling experiment.…”
Section: First Modeling Experimentsmentioning
confidence: 91%
See 2 more Smart Citations
“…3A). Laboratory observations have confirmed that the light does, indeed, enhance the growth of zoospores (Anderson et al 2003b). In the model, this effect is due to the photosynthetic activity of kleptochloroplasts of zoospores, which is consistent with experimental studies on Pfiesteria nutrient uptake 39 (C) Sensitivity of the model-estimated time period of the plateau phase of change in zoospore abundance, the maximal abundance at the plateau phase and the abundance at the end of the 14 d experiment to additional model parameters used in the third modeling experiment.…”
Section: First Modeling Experimentsmentioning
confidence: 91%
“…However, the decaying processes of the photosynthetic activity of kleptochloroplasts are not well understood. Anderson et al (2003b) assumed that the photosynthetic potential of kleptochloroplasts decreases linearly with age, eventually ceasing at a set retention time. For the sake of simplicity, we do not include the retention effect of kleptochloroplasts in this model, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high shear rate of 3 was chosen as a maximum potential value that might be encountered in an estuarine environment like Pocomoke Flats where Pfiesteria outbreaks have occurred and also because Stoecker et al (2006) show experimentally that a shear rate value of 3 has a significant negative impact on Pfiesteria feeding and growth rate. 3: From Anderson et al (2003). 4: Assuming the maximum grazing rate of TOX-A strains is substantially lower (by a factor of 3) than for NON-IND strains, based upon Burkholder et al (1997).…”
Section: Zoosporesmentioning
confidence: 99%
“…The preponderance of information on the nutritional capabilities of P. piscicida has come from studies with cultures maintained on algae for lengthy periods, presumably not actively toxic (e.g. Lewitus et al, 1999a;Eriksen et al, 2002;Feinstein et al, 2002;Anderson et al, 2003;Alavi, 2004;Lin et al, 2004). A high herbivorous growth capacity was indicated in these studies, with rapid depletion of prey, maximum growth rates ranging from 0.8 to 1.4 day À1 , and maximum ingestion rates ranging from 3 to >10 prey flagellated cell À1 day À1 .…”
Section: Introductionmentioning
confidence: 99%